Efficacy of Preoperative Portal Vein Embolization Among Patients with Hepatocellular Carcinoma, Biliary Tract Cancer, and Colorectal Liver Metastases: A Comparative Study Based on Single-Center Experience of 319 Cases - Yamashita, Suguru; Sakamoto, Yoshihiro; Yamamoto, Satoshi; Takemura, Nobuyuki; Omichi, Kiyohiko; Shinkawa, Hiroji; Mori, Kazuhiro; Kaneko, Junichi; Akamatsu, Nobuhisa; Arita, Junichi; Hasegawa, Kiyoshi; Kokudo, Norihiro (Annals of surgical oncology, 2017)
Background Efficacy of preoperative portal vein embolization (PVE) has been established; however, differences of outcomes among diseases, including hepatocellular carcinoma (HCC), biliary tract cancer (BTC), and colorectal liver metastases (CLM), are unclear. Methods Subjects included patients in a prospectively collected database undergoing PVE (from 1995 to 2013). A future liver remnant (FLR) volume ≥40% is the minimal requirement for patients with an indocyanine green retention rate at 15 min (ICGR15) <10%, and stricter criteria (FLR volume ≥50%) have been applied for patients with 20% > ICGR15 ≥ 10%. Patient characteristics and survivals were compared among those three diseases, and predictors of dropout and better FLR hypertrophy were determined. Results In 319 consecutive patients undergoing PVE for HCC ( n = 70), BTC ( n = 172), and CLM ( n = 77), the degree of hypertrophy did not significantly differ by cancer types (median 10, 9.6, and 10%, respectively). Eighty percent (256 of 319) of patients completed subsequent hepatectomy after a median waiting interval of 24 days (range 5–90), while dropout after PVE was more common in BTC or CLM (odds ratio 2.75, p = 0.018), mainly because of disease progression. Ninety-day liver-related mortality after hepatectomy was 0% in the entire cohort, and 5-year overall survival of patients with HCC, BTC, and CLM was 56, 50, and 51%, respectively ( p = 0.948). No patients who dropped out survived more than 2.5 years after PVE. Conclusion PVE produced equivalent FLR hypertrophy among the three diseases as long as liver function was fulfilling the preset criteria; however, the completion rate of subsequent hepatectomy was highest in HCC. PVE followed by hepatectomy was a safe and feasible strategy for otherwise unresectable disease irrespective of cancer types.